PERUBAHAN KOMITMEN PADA REFORMASI BIROKRASI TEMATIK DALAM PENGENTASAN KEMISKINAN DI KOTA MADIUN TAHUN 2023-2024 - Muhammad Ilham Farhan Nafis; Iyep Saefulrahman (Halu Oleo University, 2025)
This study examines changes in commitment to thematic bureaucratic reform in poverty alleviation in Madiun City in 2023-2024. Thematic bureaucratic reform is a policy innovation that emphasises the resolution of concrete problems in society, particularly poverty, through the internal transformation of government bureaucracy. This study uses a descriptive qualitative method with a cultural reform approach focused on changes in the commitment and work ethic of the apparatus. Data were collected through in-depth interviews with key informants from various regional agencies and analysis of policy documents. The results of the study show that the Madiun City Government has demonstrated its commitment through the establishment of supporting regulations, namely the Mayor's Decree on the Bureaucratic Reform Team and the Poverty Reduction Coordination Team (TKPK). Changes in commitment can be seen from efforts to improve business processes, improve data, and reformulate programs/activities to be more targeted. However, its implementation still faces obstacles in the form of data inconsistencies between institutions and suboptimal shared responsibility across all regional institutions. This study contributes to the understanding of the implementation of thematic bureaucratic reform at the local level and provides recommendations for strengthening the commitment of officials to poverty alleviation.